Reform of the Policy on Developing Lecturer Research Capacity: The Key to the Internationalization of Sugriwa Hindu State University, Denpasar - Anak Agung Made Bayu Wirama (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This policy paper analyzes the low international ranking of lecturers' research output at Sugriwa Hindu State University (UHN) Denpasar and recommends focused policy interventions to realize the internationalization program. The main problem identified stems from the lack of lecturers' capacity and competence in global research methodology, exacerbated by the misaligned training curriculum design and the lack of specific infrastructure support. The writing methodology uses Qualitative Policy Analysis with a normative-evaluative approach. The author identifies the root of the problem through a conceptual framework based on the Human Resource Capacity Development Theory (Senge, 2006) and the Research Ecosystem Theory (Teichler, 2017). Five alternative regulatory policies are identified and evaluated using William N. Dunn's Policy Evaluation Criteria (Effectiveness, Efficiency, Adequacy, Responsiveness) through a scoring method. Primary data sources come from PTKN regulations and general institutional performance data, supported by relevant academic literature (7th APA Citation). The results of Dunn's analysis indicate that the most effective policies are those that simultaneously address technical and competency barriers. The main policy recommendation is the establishment of a Rector's Regulation on Output-Based Research Human Resource Development Reform and Global Publication Infrastructure Support. This regulation should focus on two pillars: (1) Establishment of a Global Manuscript Center (GMC) to provide mandatory proofreading and mentoring, and (2) Implementation of a Mandatory Output-Based Global Research Training Curriculum (PICM) as a requirement for grant access. The implementation of this dual policy is expected to fundamentally improve lecturer competency and accelerate UHN Sugriwa's international recognition.